Corruption Factors and Discretion of the Law Enforcement Agency - Vladimir Valentinovich Kozhevnikov; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2025)
The article analyzes the corruption-generating factors enshrined in official legal documents—the Federal Law of the Russian Federation